Incident management model for a state entity - Loayza-Uyehara, Alexander Alberto (2016)
This article shows the development of an Incident Management Model based on ITIL v 3.0 that will allow the improvement of information technology services (TI) delivery, provided by the National Office of Electronic Government and Informatic (ONGEI). Due to the increase of requirements in the use of the TI services from other State entities (users), the current situation of ONGEI was analyzed in order to identify their incident management problems as well as the causes that originate them. In this way, it was identified that the severities were not foreseen, neither the response nor the restore times; it was also found the existence of duplication of registers, a new management model and the purchase of a new tool were proposed (Service Tonic, developed by a company with the same name) to adequately manage incidents and service management.